2018
DOI: 10.1177/1471301218806376
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long-term, group-based physical, cognitive and social activities on physical performance in elderly, community-dwelling people with mild to moderate dementia

Abstract: Background Elderly people with dementia are known to be less physically active compared with elderly, healthy people, emphasizing the need for interventions in order to maintain a high level of independence in activities of daily living. The aim was to evaluate the effect of long-term, group-based rehabilitation including physical activity on physical performance in elderly, community-dwelling people with mild to moderate dementia. Methods A quasi-experimental study of 18 elderly, community-dwelling people, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Attendance to the intervention was high (mean: 85%) and in line with previous studies showing that physical exercise and cognitive stimulation is acceptable components in interventions for persons with dementia (Aguirre et al, 2013;Frederiksen et al, 2014;Hoffmann et al, 2016;Spector et al, 2003;Yu and Swartwood, 2012). Results from this study correspond to previous studies showing possible cumulative effects of other kinds of multicomponent non-pharmacological interventions for people with early-stage dementia (Chalfont et al, 2020;Junge et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Attendance to the intervention was high (mean: 85%) and in line with previous studies showing that physical exercise and cognitive stimulation is acceptable components in interventions for persons with dementia (Aguirre et al, 2013;Frederiksen et al, 2014;Hoffmann et al, 2016;Spector et al, 2003;Yu and Swartwood, 2012). Results from this study correspond to previous studies showing possible cumulative effects of other kinds of multicomponent non-pharmacological interventions for people with early-stage dementia (Chalfont et al, 2020;Junge et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…One approach is physical exercise, which has shown promising results in regard of improving physical capacities such as strength, performance and exercise self-efficacy (Lee et al, 2016;Sobol et al, 2016;Telenius et al, 2015). Moreover, being physically active can improve performance of activities of daily living, reduce depressive symptoms and thereby enhance quality of life among people with dementia (Henskens et al, 2018;Huang et al, 2020;Junge et al, 2020;Nuzum et al, 2020;Potter et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review found mindfulness to be an effective intervention for improving well‐being in people living with multiple sclerosis (Simpson et al., 2019). Well‐being and dementia has been the most widely researched with evidence for the use of exercise (Junge, Knudsen, & Kristensen, 2018; Olsson, Lampic, Skovdahl, & Engström, 2013), creative activities (Windle et al., 2018), gardening (Gonzalez & Kirkevold, 2014; Hall, Mitchell, Webber, & Johnson, 2018) and music (Evans, Garabedian, & Bray, 2017; van der Steen et al., 2018) to improve self‐worth, social interaction and QoL. There is limited published research available to determine which specific meaningful activities might enhance the well‐being of plwMND.…”
Section: Introductionmentioning
confidence: 99%
“…These studies show promising but inconsistent results. For example, seven studies observed positive effects of physical activity on walking speed as assessed through short distance walk tests [17][18][19][20][21][22][23], whereas fifteen studies did not report statistically significant findings [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Furthermore, ten studies applied an instrumented gait analysis, and mainly reported positive effects of physical activity on stride length [39][40][41][42][43][44][45][46], stride time [43,45], step time [46], double support time [40], and stride frequency [41].…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistent results exist for walking speed [40][41][42][43][44][46][47][48], stride speed [39,45], percent of double support [43][44][45], and cadence [19,39,42,43,45,46]. Findings of studies investigating dual task conditions are also inconsistent regarding potential effects on gait impairments and do not allow meaningful conclusions [26,28,35,36,39,45]. Thus, more research is needed to better understand the potentially beneficial effects of physical activity on gait performance in IWD in both single and dual task conditions.…”
Section: Introductionmentioning
confidence: 99%